L’infermiere nel carcere: un’opportunità di rapporto con il detenuto - Ballesi, Stefania; Trimboli, Domenico Francesco (Il sogno della farfalla, 2022)
The aim of this article is to discuss the detainees’ right to mental health in jails through the perspective of nursing professionists. On the basis of their personal experience in the roman Rebibbia prison, the authors highlight the difficulties encountered by the nursing personnel in affirming their role. A particular attention is focused on the medical and strictly psychiatric skills required in penitentiary institutions. The complexity of the relationship with the detainees requires a teamwork involving many different health care figures and prison’s officers to guarantee an effective approach. The authors finally underline the importance to guarantee an adequate personal and professional training to the nursing personnel.